Spatial imbalance and factors influencing carbon emission efficiency in China’s transport industry - Ma, Qifei; Jia, Peng; Kuang, Haibo (Frontiers in Earth Science, 2022)
To promote the ability of the transport industry to achieve carbon neutrality, explore the regional differences of transport carbon emissions efficiency (TCEE) and accurately identifying its influencing factors are necessary. We measured the TCEE of 30 provinces in China from 2003 to 2018, and its spatial imbalance and influencing factors were determined. Previous studies have shown that the TCEE is increasing at an overall low level with significant regional differences. The total regional differences of China’s TCEE showing a trend of rising first and then falling, the intra-regional differences are the main source of total differences. This study showed that certain factors, such as the economic level, transport structure, energy structure, and technical level, significantly influenced the TCEE, but there were notable spatio-temporal differences in each factor. Finally, targeted and differentiated carbon emissions reduction policies were proposed for transport departments to realise carbon neutrality as rapidly as possible.